Mycorrhizal Fungal Partners Remain Constant during a Root Lifecycle of Pleione bulbocodioides (Orchidaceae) - Jiao Qin (MDPI AG, 2021)
Mycorrhizal mutualisms are vital for orchids through germination to adulthood. Fungal species diversity and community composition vary across seasons and plant development stages and affect plant survival, adaptation, and community maintenance. Knowledge of the temporal turnover of mycorrhizal fungi (OMF) remains poorly understood in the eco-physiologically diverse orchids (especially in epiphytic orchids), although it is important to understand the function and adaptation of mycorrhizae. Some species of Pleione are epiphytic plants with annual roots and may recruit different fungal partners during their root lifecycle. Based on continuous samplings of Pleione bulbocodioides during a whole root lifecycle, we characterized the fungal temporal dynamics using Illumina sequencing of the ITS2 region. Our data showed that the plants of P. bulbocodioides were quickly colonized by OMF at root emergence and had a constant OMF composition throughout one root lifecycle, although the OMF richness declined with root aging after a peak occurrence during root elongation. In contrast, the richness of root-inhabiting fungal endophytes kept increasing with root aging and more drastic turnovers were found in their species compositions. Our findings of OMF temporal turnover contribute to further understanding of mycorrhizal associations and adaptation of Orchidaceae and will benefit orchid resource conservation and utilization.